The caries-related cost and effects of a tax on sugar-sweetened beverages - Jevdjevic, Milica; Trescher, Anna-Lena; Rovers, Maroeska; Listl, Stefan (Public health, 2019)
OBJECTIVES: While taxes on sugar-sweetened beverages (SSBs) have frequently been proposed to reduce non-communicable diseases like obesity and type 2 diabetes, relatively little is known about the caries-related impacts of SSB taxation. We assessed the effect of a 20% ad valorem tax on SSBs on dental caries and related treatment costs, specifically taking into account that consumers may switch from SSBs to other (non-taxed) sugar-containing drinks. - STUDY DESIGN: Cost-effectiveness analysis. - METHODS: A tooth-level Markov model was developed to evaluate the cost and effects of SSB taxation. Tax-related changes in sugar consumption were calculated using available evidence on SSBs price and cross-price elasticities, thereby taking changes in drinks consumption behaviors into account. The model was used to establish lifetime disease-free tooth years, caries lesions prevented, caries-related treatment costs avoided, tax revenues, and administrative costs (reference case: the Netherlands). Deterministic and probabilistic sensitivity analyses were performed to address uncertainties. - RESULTS: A 20% SSB taxation would result in an average of 2.13 (95% uncertainty interval [UI] 2.12-2.13) caries-free tooth years per person and, on population level, prevention of 1,030,163 (95% UI 1,027,903-1,032,423) caries lesions. The intervention was found to save an aggregate total of € 159.01 (95% UI 158.67-159.35) million in terms of dental care expenditures. The estimated lifetime tax revenues (€3.49billion) were larger than the administrative costs for taxation (€37.3 million). - CONCLUSIONS: Our results show that SSB taxation may substantially improve oral health and reduce the caries-related economic burden. Benefits would be the greatest for younger age groups.